The social construction of climate change power, knowledge, norms, discources - Pettenger, Mary E. (Global environmental governance, 2007)
Adopts two constructivist perspectives, norm-centred and discourse, to explore social construction of climate change. This book offers an understanding of why efforts to mitigate climate change have failed. It aims to provide academics and policy makers with an understanding of this important topic.